EXPIRATORY FLOW RATE CHANGES DURING MENSTRUAL CYCLE - Arora, Dimple Bajaj; Sandhu, Parminder Kaur; Mehta, Kiran; Kaur, Anterpreet; Kaur, Nimarpreet (Pakistan Journal of Physiology, 2015)
The dynamic changes in the level of various hormones during different phases of menstrual cycle are known to affect various functions of the body, apart from the reproductive system. This study was intended to confirm the probable effects of follicular, secretory and menstrual phases on pulmonary functions. Methods: The study was conducted in the Department of Physiology, Indira Gandhi Medical College Shimla. Study involved 40 women in the reproductive age group. Spirometry was done in various phases of menstrual cycle and compared. Results: The mean value of lung function tests, i.e., forced vital capacity (FVC), forced expiratory volume in 1st second (FEV1), FEV1/FVC ratio, and the forced expiratory flow 25% to 75% (FEF25–75) in secretory phase were significantly higher than in menstrual phase (p<0.05). The PFTs in menstrual phase were even lower than in follicular phase (p<0.04). Conclusion: Respiratory parameters of women in reproductive age group show significant variation during different phases of menstrual cycle.